The effect of cooperative group investigation in student’s reading comprehension - Uswatun Hasanah (Graduate Program, University of Islam Malang, 2020)
AbstrackThis study is to find out whether the use of Group investigation (GI) method in studets’ reading comprehension is effective or not. This research was done on the student of the ten grade, Senior High School in SMK N 2 Kediri, which have three classes. The ten grade of SMK N 2 Kediri was divided into three classes. There were class X A, X B, and X C. the researcher used X C as an experimental class and X B as control class. Reading test was the data which is collect as an instrument. Kuder Richardson 21 formula was used to get reliability. The result was 0.81, so the test was reliable. ANCOVA was used to analysed the data. The result of the analysis indicate that the students’ reading comprehension ware significanly higher. The result 0.002 it is lower than 0.05 (0.000<0.05). it is conclude that using Cooperative Group Investigation is effective in students’ readingcomprehension.Keywords: reading comprehension, group Investigation (GI).